Consumers' Intention to Adopt Internet Banking : An Indian Perspective - Nagdev, Kritika; Rajesh, Anupama (Indian Journal of Marketing, 2018)
Purpose : The purpose of this paper was to propose an Internet banking (IB) adoption model for emerging markets based on an Indian framework. It explored the role of accessibility, corporate image, demographic characteristics, perceived ease of use, perceived usefulness, self-efficacy, trust, and website quality in framing consumers' intention to use IB. Design/Methodology/Approach : Based on existing literature, 31 predictor variables were tested for the study. Cronbach's alpha test and factor loading estimates were used to assess the construct reliability and convergent validity of the scale. The data were collected through a self-administered questionnaire from a convenient sample of 250 retail bank customers. Exploratory factor analysis and multiple regression techniques were applied to the data obtained. Findings : Of the 31 predictor variables tested, 25 were found to be significant for the study. Additionally, out of the seven factors obtained, three of them were found to significantly impact IB-adoption in India. These were Perceived Usefulness, Perceived Ease of Use and Trust, and Perceived Quality. The study also indicated low adoption of Internet banking in India. Practical Implications : The results affirmed the applicability of the technology acceptance model (Davis, 1989). The three significant factors in the study can help in formulating customer engagement strategies to accept and use IB services in India. The utmost significant inference for the Indian banking industry is not only to provide hassle-free IB services, but to also build a relationship with its customers based on trust and provide a fast and easy to access website portal. Originality/Value : The model formulated established the level of acceptance for IB in India, which is a valuable contribution to the adoption theories across the globe. The extended model can be further tested to segment retail bank customers of India on the basis of their intention to use Internet banking.